2013
DOI: 10.15376/biores.9.1.801-815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weed Control and Fertilization on Wood and Chemi-mechanical Pulp Properties of a Populus deltoides Clone

Abstract: Weed control and fertilization usually lead to an increase in the growth rate of trees and, consequently, to a possible modification of the quality of the wood and its end products. The effect of weed control and fertilization practices were determined on tree growth parameters, wood density, fiber weight, fiber length, and chemical wood composition, as well as the chemi-mechanical pulp properties, for 8-year-old Populus deltoides `Delta Gold´ grown in Argentina. Four treatments belonging to a randomized compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Novaes et al (2009) reported an increase in cellulose and hemicelluloses and a decrease in lignin by applying NPK to poplar seedlings. Villegas et al (2014) also observed an increase in cellulose and a decrease in lignin by applying NPK to poplar seedlings.…”
Section: Chemicals Measurementsmentioning
confidence: 71%
“…Novaes et al (2009) reported an increase in cellulose and hemicelluloses and a decrease in lignin by applying NPK to poplar seedlings. Villegas et al (2014) also observed an increase in cellulose and a decrease in lignin by applying NPK to poplar seedlings.…”
Section: Chemicals Measurementsmentioning
confidence: 71%